Sustainable supply chain management – past, present and future - Tundys, Blanka (Zarządzanie zrównoważonym łańcuchem dostaw – przeszłość, teraźniejszość i przyszłość, 2020)
Sustainable supply chain management has been an issue in both literature and business practice since the 1990s. Both the development phases and the definition range (including the complexity and number of individual processes) have been subject to changes and modifications over the years. The multitude of definitions and theoretical scope is a barrier to the implementation of the concept in economic practice. The aim of this paper is to show how it has evaluated the concept and thematic scope in theoretical point of view and in relation to its practical implementation. The research was carried out using content analysis methods, as well as selected case studies. The most important findings include: a presentation and change in the understanding and application of SSCM; bibliometric analysis with an interpretation of the state, volume and scope of SC research; directions and trends in research including the identification of research gaps that may be a basis for further research
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 3, s. 187-207
Keywords: sustainable supply chain management; theory; praxis; bibliometric analysis; zarządzanie zrównoważonym łańcuchem dostaw; teoria; łańcuch dostaw; zarządzanie łańcuchem dostaw; praktyka; analiza bibliometryczna